(3TgGOJj(B... (3CMeO CHh GdZjW (B:s (3GdSjGSI GdNGQLjI GdeUQjI (B2004-2011 /s - (3CHh GdZjW, CMeO,s 1942- ((3GdLjRI, eUQ (B:s (3OGQ fgVI eUQ ddfTQ,s, 2021)
(3gPG GdcJGH TgGOJj gh TgGOI hRjQ GdNGQLjI CMeO CHh GdZjW, BNQ hRjQ NGQLjI aj Mce eHGQc bHd GdKhQI, hajg jJMOK Yf UfGYI GdbQGQ GdeUQj hjQO Ydi GdGJgGeGJ GdehLgI dSjGSjI GdNGQLjI hJQOj OhQgG aj fgGjI YUQ eHGQc, gPG GdcJGH gh ePcQGJ hRjQ GdNGQLjI CMeO CHh GdZjW aj GdSjGSI GdNGQLjI GdeUQjI (B2004-2011(3, cja cGf CSdhH GJNGP GdbQGQ aj eUQ hbJ Mce eHGQc, eG MbjbI JQGLY GdOhQ GdeUQj hJCKjQg aj GdefWbI hGdYGde, gd JNdi fXGe eHGQc Yf eSdeGJ GdSjGSI GdNGQLjI GdeUQjI aj HDQ GdJhJQ hGdUQGY dCWQGa CNQi dGYHI MGhdJ SQbI OhQ eUQ, eG MbjbI eG MOK aj eUQ aj GdCjGe GdCNjQI dMce GdQFjS GdeUQj GdSGHb, eGPG bGd YeQ SdjeGf Yf eMGhdI GZJjGdg bHd JfMj eHGQc, hgd cGf eHGQc jJhbY GdNjGfI ef LGfH GdhdGjGJ GdeJMOI GdCeQjcjI, CSFdI YOjOI hZjQgG GdcKjQ jRjM GdZehV YfgG HGdELGHI YdjgG hRjQ GdNGQLjI GdCSHb CMeO CHh GdZjW(B.s
(3ETQGa YGe (B: (3OGdjG eMeO EHQGgje ; JUeje GdZdGa (B: (3cQje BOe(B.s
(3edGMb (B: (3UaMI (B513-536.s
Keywords: (3CHh GdZjW, CMeO,s -- 1942- -- (3jhejGJs; (3eUQs -- (3YdGbGJ NGQLjIs -- (3MSfj eHGQc, (B1981-2011s -- (3eQhjGJ TNUjIs; (3eUQs -- (3SjGSI hMcheIs -- (3MSfj eHGQc, (B1981-2011s -- (3eQhjGJ TNUjIs; (3eUQs -- (3SjGSI hMcheIs -- (3GdKhQI, (B2011s -- (3eQhjGJ TNUjIs